Calibration Systematics in the Search for Cosmic Reionisation - Joseph, Ronniy Christoffer (Curtin University, 2020)
The Epoch of Reionisation (EoR) holds the key to our understanding of the first luminous sources in the Universe. The latest generation of low frequency radio interferometers have opened a direct window into the EoR. However, experiments searching for a signal from the EoR are sensitive to bias. This thesis explores the impact of various errors in the calibration of EoR instruments and our ability to detect a signal from these early times.